PESTEL Analysis of the Integration of Tourist Visa Policies in the Kepulauan Riau - Lubis, Arina; Amalia, Eva (Program Studi Ilmu Administrasi Negara FISIP UMRAH, 2025)
Tourism is a key economic sector in Indonesia, with the Riau Islands being a major destination due to its proximity to Singapore and Malaysia. However, its tourism growth is hindered by restrictive visa policies, including high Visa on Arrival (VoA) fees and frequent regulatory changes, making it less competitive than neighboring countries. This study analyzes the impact of visa policies on Riau Islands tourism using the PESTEL framework (Political, Economic, Social, Technological, Environmental, and Legal). A qualitative descriptive method was applied, utilizing secondary data from government reports, academic studies, and case analyses. The findings indicate that frequent visa policy shifts create uncertainty for tourists and businesses. Economically, high VoA fees deter short-term visitors, particularly from Singapore and Malaysia. Socially, travelers prefer destinations with simpler visa procedures, while cases of visa misuse highlight the need for stricter controls. Technological limitations in e-Visa processing and border control contribute to inefficiencies. Environmentally, rising tourist numbers risk over-tourism and ecological degradation. Legally, inconsistent enforcement across entry points causes confusion. To improve competitiveness, this study recommends lowering VoA costs, expanding visa exemptions, enhancing digital visa services, and integrating sustainability into visa policies. While this study offers valuable insights, it lacks quantitative data and direct stakeholder input. Future research should incorporate statistical models to measure visa policy impacts and compare Indonesia’s policies with regional competitors. A balanced, technology-driven, and well-regulated visa policy can position the Kepulauan Riau as a leading sustainable tourism destination in Southeast Asia.